The role of the legal information officer - Harvey, Trevor, 1955-; ScienceDirect eBooks (Oxford, England : Chandos Pub., 2003)
This is a no-nonsense book, written by a leading authority. It covers the ever-changing role of the information officer and how to survive. It discusses such issues as: what does a law information officer do on a day-to-day basis and the mechanics and processes for supplying information; a practical guide to enquiries and undertaking research; and how to set up and manage an information service. Importantly, the author does not take a 'dry' approach to the subject; rather, he discusses the following contentious issues: given the amount of information available on lawyers' PCs, are information officers really necessary?; when should the information officer undertake the research and when should the lawyer do it; will information officers become redundant as the role of the professional support lawyer becomes more important. In essence, the book analyses the changing role of the law information officer and serves as a practical survival guide. Based on practical, day-to-day experienceJargon free; no 'high-faluting' theoriesExamines the threat (if such it be) of professional support lawyers.
1. Information roles and information sources -- 2. Managing and recruiting -- 3. Marketing and promoting your service -- 4. Research and enquiries -- 5. The internet: threat or opportunity? -- 6. You say taxonomy, I say classification -- you say thesaurus, I say classification -- 7. Know-how and knowledge management -- 8. Copyright -- 9. You're on your own now -- 10. The future for the legal information professional.
Includes bibliographical references (pages 185-187) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Elsevier
Keywords: Law libraries; Legal research; Law libraries -- Great Britain; Law firms -- Great Britain; Legal research -- Great Britain; Bibliothécaires de droit; Droit -- Documentation, Services de; Cabinets d'avocat -- Documentation, Services de; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- Archives & Special Libraries; Law firms; Law libraries; Legal research; Great Britain; Rechtswetenschap; Informanten; Electronic books